Fundamentals of Psychological Disorders - Bridley, Alexis; Daffin Jr., Lee W. (Open textbook library., 2018)
Fundamentals of Psychological Disorders (formerly Abnormal Psychology) is an Open Education Resource written by Alexis Bridley, Ph.D. and Lee W. Daffin Jr., Ph.D. through Washington State University. The book tackles the difficult topic of mental disorders in 15 modules and is updated through the DSM-5-TR. This journey starts by discussing what abnormal behavior is by attempting to understand what normal behavior is. Models of abnormal psychology and clinical assessment, diagnosis, and treatment are then discussed. With these three modules completed, the authors next explore several classes of mental disorders in 5 blocks. Block 1 covers mood, trauma and stressor related, and dissociative disorders. Block 2 covers anxiety, somatic symptom, and obsessive-compulsive disorders. Block 3 covers eating and substance-related and addictive disorders. Block 4 tackles schizophrenia spectrum and personality disorders. Finally, Block 5 investigates neurocognitive disorders and then ends with a discussion of contemporary issues in psychopathology. Disorders are covered by discussing their clinical presentation and DSM Criteria, epidemiology, comorbidity, etiology, and treatment options.